Superparamagnetic Fe3O4@CA Nanoparticles and Their Potential as Draw Solution Agents in Forward Osmosis - Irena Petrinic (MDPI AG, 2021)
In this study, citric acid (CA)-coated magnetite Fe3O4 magnetic nanoparticles (Fe3O4@CA MNPs) for use as draw solution (DS) agents in forward osmosis (FO) were synthesized by co-precipitation and characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), dynamic light scattering (DLS), transmission electron microscopy (TEM) and magnetic measurements. Prepared 3.7% w/w colloidal solutions of Fe3O4@CA MNPs exhibited an osmotic pressure of 18.7 bar after purification without aggregation and a sufficient magnetization of 44 emu/g to allow DS regeneration by an external magnetic field. Fe3O4@CA suspensions were used as DS in FO cross-flow filtration with deionized (DI) water as FS and with the active layer of the FO membrane facing the FS and NaCl as a reference DS. The same transmembrane bulk osmotic pressure resulted in different water fluxes for NaCl and MNPs, respectively. Thus the initial water flux with Fe3O4@CA was 9.2 LMH whereas for 0.45 M NaCl as DS it was 14.1 LMH. The reverse solute flux was 0.08 GMH for Fe3O4@CA and 2.5 GMH for NaCl. These differences are ascribed to a more pronounced internal dilutive concentration polarization with Fe3O4@CA as DS compared to NaCl as DS. This research demonstrated that the proposed Fe3O4@CA can be used as a potential low reverse solute flux DS for FO processes.